Just-in-Time Elements and Benefits - García Alcaraz, Jorge Luis.; Macías, Aide Aracely Maldonado; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book reports the elements required for implementing Just in Time (JIT) technique in companies. The main reasons for low implementation processes and the main benefits from the successful implementation of them are highlighted in this book. Structural equation models are presented to help identify the essential elements in JIT.
JIT concepts -- Method for analysis -- JIT elements -- JIT benefits -- Reasons for low JIT implementation process -- Structural equation models associating JIT elements and its benefits -- Structural equations models associating reasons for low JIT implementation and benefits.
Keywords: Industrial Management; Production management; Manufactures; Industrial Management; Operations Management; Machines, Tools, Processes